Design technology of students’ sports training based on martial arts classes in physical education at the university: theoretical aspect - Rakovetsky A.I.; Ponomarev V.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate and develop program and methodological content of the technology for designing sports training for female students based on martial arts classes in physical education at the university and recommend it for practice. Methods and structure of the study. The experimental base of the research is the Russian Timiryazev State Agrarian University. Over the course of two years, a sociological survey and questionnaire survey of students and teachers of the university was conducted on the subject of designing a sports-specific approach to physical education of modern student youth. Also, an analysis of scientific and methodological literature on the topic of the study was carried out, factual material was formed, and the theoretical content of the experimental technology for designing sports training for female students in physical education at the university was built and filled. The program and methodological support of the pedagogical technology of designing sports training for female university students based on martial arts classes was developed. The organizational and methodological algorithm for including sports training for female students in physical education at the university was formed. Results and conclusions. Based on the preliminary theoretical study, it was revealed that only no more than 10% of students from the total number of students are involved in sports at the university, including 3% of girls. At the same time, the Government of the country has planned the need to involve up to 70% of student youth in active physical education and sports by 2030. The conducted sociological analysis and survey showed that 80% of teachers and 90% of students are not against physical education at the university being sport-oriented. Based on the results of the conducted theoretical study, a program and methodological support for the pedagogical technology of sports training for female students based on martial arts classes in physical education at the university was developed. Also, an organizational and methodological algorithm for the implementation of theoretical developments of experimental technology in physical education at the university has been formed.